Long term effects of different training modalities on power, speed, skill and anaerobic capacity in young male basketball players - Balciunas, M.; Stonkus, S.; Abrantes, C.; Sampaio, J. (Journal of Sports Science & Medicine, 2006)
The purpose of this study was to identify the effect of 4 months of different training modalities on power, speed, skill and anaerobic capacity in 15-16 year old male basketball players. Thirty five Lithuanian basketball players were randomly assigned into three groups: power endurance group (intermittent exercise, PE, n = 12), general endurance group (continuous exercise, GE, n = 11) and control group (regular basketball training, CG, n = 12). The power endurance model was based in basketball game external structure whereas the general endurance model was based in continuous actions that frequently occur during the basketball game. The training models were used for 16 weeks in sessions conducted 3 times a week during 90 minutes each in the competition period. The following tests were performed: 20 m speed run, Squat jump, Countermovement jump, Running-based Anaerobic Sprint Test (RAST), 2 min. shooting test and the Shuttle ball-dribbling test. A 3~2 repeated measures ANOVA revealed no statistically significant differences in the 20 m speed run, Squat jump and Countermovement jump (p > 0.05). On the other hand, RAST showed significant increases in PE, with greater increases during the 5th and 6th runs. The PE training model also produced a significant improvement in the shuttle ball-dribbling test (48.7}1.5 in the pretest, 45.5}1.3 in the posttest, p . 0.05). Globally, our results suggest that both training modalities were able to maintain initial values of speed and power, however, the anaerobic capacity and skill increased only in the players from the power endurance group. Therefore, the power endurance training (intermittent high intensity exercise) may be more beneficial to prepare junior players according to the game cardiovascular and metabolic specific determinants.